مشاهدة الأفلام العربية (بالعناوين الفرعية) واثرها في عدد المفرادات المكتسبة = Watching Arabic movies (with subtitles) and the effect on number of vocabulary acquisition - Daud, Nadwah; Bahari, Nik Nur Hidayah (Persatuan Bekas Mahasiswa Islam Timur Tengah, 2020)
This research aims at looking into the effectiveness of watching Arabic films on Arabic language learning as a second language in term of vocabulary size. It is a semi-experimental with pre- and post-test design, with purposive sampling of 60 male and female respondents were the students of International Islamic University Malaysia (IIUM) studied Arabic language at the Center of Language and Pre-University Academic Development (CELPAD). The instrument of the study was Vocabulary Knowledge Scale (VKS) and the analysis of covariance (ANCOVA) was used in order to eliminate effects related to possible associated variable. The result indicated that the number of vocabulary gained by the experimental group is significantly higher than the control group.